GREEN GARDEN LEARNING: PENDIDIKAN LINGKUNGAN MELALUI PRAKTIK MEMUPUK DAN MENATA TANAMAN DI DESA BANGUN SARI - Butarbutar, Imelda; Sianipar, Nelly Noviana; Manurung, Putri Tresia; Sembiring, Sherly Adelia; Waruwu, Nurwian (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2025)
This study aims to improve public understanding of practical training in arranging plants effectively so that green spaces can be utilized optimally and aesthetically in Bangun Sari Village, Tanjung Morawa District, Deli Serdang Regency, which is carried out by students of HKBP Nommensen University Medan through the implementation of Community Service. Green Garden Learning: Environmental Education through the Practice of Fertilizing and Arranging Plants in Bangun Sari Village adopts a participatory method as the main approach in implementing this program. The participatory method provides space for the community to become active partners in every stage of the community service activity. This approach is intended to increase involvement and a sense of ownership of the program, as well as ensure that the activities carried out are in accordance with the needs and aspirations of the local community. By involving the community in the planning, implementation, and evaluation processes, this program is expected to provide a more real and sustainable impact. Based on the results obtained during the Green Garden Learning program, it can be concluded that this activity has a positive impact on the cleanliness, orderliness, and fertility of the garden environment. Students involved in this program not only gain practical experience in plant management but also increase their understanding of the importance of proper care in farming.